Cardiac Rehabilitation Manual - Niebauer, Josef (Springer International Publishing : Imprint: Springer, 2017)
This book fulfills the need for practical guidance among all professionals involved in the management of these patients, from residents and fellows of cardiology and internal medicine, surgical teams, physiotherapy professionals, critical care physicians and family medicine practitioners. The thoroughly updated content takes into account recent developments in cardiac rehabilitation, and incorporates practical advice on how to use guidelines in clinical practice. There will be one new chapter on patients with cardiac resynchronization therapy and all the others will be updated to keep up-to-date with the guidelines and current practice. Cardiac rehabilitation is of key importance to ameliorate long-term morbidity and mortality resulting from cardiac diseases and events. However, much of the current literature is dense, unwelcoming and academic in style and format. For those physicians understanding the scope of cardiac rehabilitation there is a need to distill the guidelines and various management options available to them into a concise practical manual. Up until now, all references have looked at the general options, but there is definite need to investigate the practicalities of individual patient groups.
Keywords: Medicine.; Cardiology.; Rehabilitation.; Cardiac surgery.; elektronické knihy; electronic books